JR20, a novel natural product-derived compound, exhibits potent anti-biofilm activity against methicillin-resistant Staphylococcus aureus - Zhao, Meirong; Zhang, Chaowei; Jaiswal, Yogini; Xie, Xinrong; Huang, Dongyu; He, Zhendan; Williams, Leonard; Guan, Yifu; Bian, Hedong; Song, Xun (Frontiers in Microbiology, 2026)
ObjectiveJR20, a novel sesamin-derived arylnaphthalene lignan, has demonstrated potent antifungal activity. This study further investigates its antibacterial potential against MRSA (methicillin-resistant Staphylococcus aureus).MethodsThe highlights of this research include the use of SYTO9 and PI fluorescence double staining, along with three-dimensional confocal microscopy to reveal the thickness and viability of biofilms under JR0′s influence. Additionally, scanning and transmission electron microscopy were employed to observe the morphological changes of MRSA under JR0′s impact. By combining the observed reduction in ATP content within MRSA, a preliminary mechanism was hypothesized. In vivo anti-infection experiments were further conducted to evaluate the compound's biological activity in liver and spleen tissues of mice.ResultsJR20 exhibited potent anti-MRSA activity (IC50 = 20.88 μg/mL). Mechanistic investigations revealed multi-level effects: confocal microscopy demonstrated altered biofilm thickness and viability; SEM/TEM confirmed distinct morphological changes in bacterial cells; And ATP content reduction indicated metabolic disruption. In vivo experiments validated these antibacterial effects and further revealed anti-inflammatory properties, underscoring JR0′s therapeutic potential against MRSA infections.ConclusionThis study confirms JR0′s potent anti-MRSA activity, clarifies its effects on biofilms and MRSA morphology, and proposes a preliminary mechanism by reduced ATP. JR20 demonstrates significant potential for combating drug-resistant bacteria and advancing antibiofilm drug discovery.